Quantitative ubiquitylomics approach for characterizing the dynamic change and extensive modulation of ubiquitylation in rice seed germination. (11th December 2019) - He, Dongli; Li, Ming; Damaris, Rebecca N.; Bu, Chen; Xue, Jianyou; Yang, Pingfang
Summary: During seed germination, cells embark on extensive post‐transcriptional and post‐translational modifications (PTM), providing a perfect platform to study these events in embryo rebooting from relative quiescenct to highly active state. PR‐619, a deubiquitylase inhibitor, delayed the rice seed germination and resulted in the accumulation of ubiquitylated proteins, which indicated the protein ubiquitylation is involved in this process. Using the K‐Ɛ‐GG antibody enrichment method integrated with high‐resolution mass spectrometry, a list of 2576 lysine ubiquitylated (Kub) sites in 1171 proteins was compiled for rice embryos at 0, 12 and 24 h after imbibition (HAI). Of these, the abundance of 1419 Kub sites in 777 proteins changed significantly. Most of them substantially increased within the first 12 HAI, which is similar to the dynamic state previously observed for protein phosphorylation, implying that the first 12 HAI are essential for subsequent switch during rice seed germination. We also quantitatively analyzed the embryo proteome in these samples. Generally, a specific protein's abundance in the ubiquitylome was uncorrelated to that in the proteome. The differentially ubiquitinated proteins were greatly enriched in the categories of protein processing, DNA and RNA processing/regulation related, signaling, and transport. The DiGly footprint of the Kub sites was significantly reduced on K48, a linkage typically associated with proteasome‐mediated degradation. These observations suggest ubiquitylation may modulate the protein function more than providing 26S degradation signals in the early stage of rice seed germination. Revealing this comprehensive ubiquitylome greatly increases our understanding of this critical PTM during seed germination. Significance Statement: During germination, the matured seeds experience a complex transition from relative static to active status. Protein ubiquitylation is involved in various cellular signaling processes. However, no systemic studies of ubiquitylation on seed germination have been conducted until now. This study comprehensively quantified the ubiquitylome and characterizes extensive modulation of ubiquitylation in the embryo during rice seed germination, which will facilitate the in‐depth functional exploration of ubiquitylation in plants.